Microscopic calculations of Λ single-particle energies - Usmani, Qamar N.; Bodmer, A. R. (Elsevier Science, 1998)
A binding energy data for total baryon number A ≤ 208 and for Λ angular momenta ℓΛ ≤ 3 are analyzed in terms of phenomenological (but generally consistent with meson-exchange) ΛN and ΛNN potentials. The Fermi hypernetted chain technique is used to calculate the expectation values for the Λ binding to nuclear matter. Accurate effective ΛN and ΛNN potentials are obtained which are folded with the core-nucleus nucleon densities to calculate the Λ single-particle potential UΛ (r). We use a dispersive ANN potential but also include an explicit ρ dependence to allow for reduced repulsion in the surface, and the best fits have a large ρ dependence giving consistency with the variational Monte Carlo calculations for 5ΛHe. The exchange fraction of the ΛN space-exchange potential is found to be 0.2-0.3 corresponding to m*Λ ≃ (0.74 - 0.82)mΛ. Charge-symmetry breaking is found to be significant for heavy hypernuclei with a large neutron excess, with a strength consistent with that obtained from the A = 4 hypernuclei.